THE EFFECTIVENESS OF ELLEN’S TALKSHOW ON YOUTUBE TO IMPROVE CRITICAL LISTENING SKILL AT X ACCOUNTING 2 OF SMKN 2 NGANJUK - Lorensa Dian Anggrain; Sujono; Wuri Cahyanti (STKIP PGRI Nganjuk, 2024)
The purpose of the study are to : To find out student’s critical listening skill before taught by using Ellen’s Talkshow on YouTube, to find out student’s critical listening skill after taught by using Ellen’s Ttalkshow on YouTube, to analyze the significant different on students’ critical listening skill before and after taught by using Ellen’s Talkshow on YouTube in the teaching listening. This research is Quasi- Experimental with one group pre – test, post – test. The research was done at SMKN 2 Nganjuk for the academic year of 2022/2023, by using population whole tenth grade, the sample used by the researcher is the class X Accounting 2, that consists of 36 students. The technique of sampling is using purposive sampling. The collecting data in this research by using test. The technique of analysis data used to analyze the data in this research is Mean, Median, Mode, standart deviastion and T – Test. The results of this study are consistent with the reseacher hypothesis that low student critical listening skills with the student's test scores before using the teen Ellen's talkshow on youtube show averaged 51 - the value of pre-test students is 51, with a high value of 75 and a low value of 25 student critical listening skills began increasing with the student's test scores after using Ellen's talk show on youtube showed the average - post value - test 86, With the highest score of 100 and the lowest score of 40 significant and visible differences through t-count 2.289, whereas t-table is 1,690, then t-count > t-table, meaning ho is rejected and ha is accepted. So